Pemeriksaan Material pada Pembangunan Rumah Non-Engineered di Daerah Rawan Gempa Dusun Serut, Palbapang Kabupaten Bantul, Yogyakarta - Zulfiar, Muhammad Heri (Semesta Teknika, 2018)
Bantul Regency is a region with high level of seismic activity in Indonesia. Buildings that have the highest risk of collapse to earthquake are non-engineered buildings or residential buildings built without planning or not according regulation. This study aims to know contruction practices and material examination on non-engineered buildings in earthquake prone areas in accordance with the Indonesian National Standard. The object research is the construction of non-engineered building in Serut Village, Palbapang, Bantul Regency. The testing of material construction materials include: concrete test, reinforcing steel test and bricks test. the material are tested on the laboratory of Universitas Muhammadiyah Yogyakarta.  The observations and measurements to the practices of construction consist of: concrete sloof with size 15 × 20 cm with the main reinforcement 4Ø12 and beugel reinforcement Ø6-150; column with size 10 × 15 cm with main reinforcement 4Ø10 and beugel reinforcement Ø6-150; the concrete mixture is made manually with a composition 1 cement: 3 sand: 2 gravel; Brick size 4.35 cm x 12.036 cm x 23.902 cm class criteria M-6 module. Laboratory material test results showed: steel reinforcement diameter Ø 10 mm obtained tensile strength (fy) 401.52 Mpa; Ø12 mm diameter obtained tensile strength (fy) 393,736 M.Pa; concrete have average compressive strength of 181 kg/cm2; brick test have average compressive strength of 20.03 kg/cm2. The conclusion of contruction practices on non-engineered buildings in earthquake prone areas are adequate on major earthquake, the quality of construction concrete and reinforcing steel are fulfilling the criteria and requirements of the Indonesian National Standard, but quality of material brick is not adequate standar.